Effective English Language Instruction Using Cognitive Linguistics in English Departments (Eurasian Journal of Research, Development and Innovation, 2023)
The current study begins with a brief introduction to the fundamental principles of cognitive linguistics, outlining Goldberg's construction of grammar as a significant theory evolving within the cognitive linguistic approach to the grammatical level of language structure. It then proceeds to consider how cognitive linguistics' various syntactic and lexical findings might be successfully applied to language education in English departments. The paper draws on a range of authors' explorations of the practical application of cognitive linguistics to second language instruction and the relevant theoretical literature. It provides a list and evaluation of ELT books that incorporate these ideas.